(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Metabolic syndrome (MetS) is a complex and multifactorial disorder characterized by a cluster of metabolic abnormalities, including insulin resistance, central obesity, dyslipidemia, hypertension, and impaired glucose tolerance. Over recent decades, the global prevalence of MetS has risen significantly, posing a major public health challenge due to its strong association with cardiovascular diseases, type 2 diabetes mellitus, and various organ dysfunctions. Among the less frequently studied but clinically significant manifestations of MetS is gastric ischemia, which results from compromised blood flow to the stomach tissue, leading to cellular hypoxia and tissue injury. Gastric ischemia in the context of MetS is primarily attributed to systemic vascular dysfunction, endothelial impairment, and microcirculatory disturbances caused by chronic metabolic derangements. These pathological changes provoke a cascade of events including inflammation, oxidative stress, and apoptosis within the gastric mucosa, which may exacerbate tissue damage and compromise gastric function. The clinical consequences of gastric ischemia can range from mild dyspeptic symptoms to severe complications such as gastric ulceration, bleeding, and impaired mucosal regeneration. Understanding the prognosis and potential complications of gastric ischemia in patients with MetS is crucial for developing effective diagnostic, preventive, and therapeutic strategies. Despite increasing recognition of the importance of ischemic processes in MetS, the literature on long-term outcomes and complications specific to gastric ischemia remains limited. This gap highlights the need for comprehensive research focusing on the pathophysiological mechanisms, clinical progression, and potential interventions to mitigate adverse outcomes in this patient population. Therefore, the present study aims to critically evaluate the prognosis and complications associated with gastric ischemia in metabolic syndrome, integrating current evidence from morphological, immunohistochemical, and clinical investigations to enhance the understanding of this complex interplay and guide future clinical practice.